PEI-coated HPAN / COF nanofiber ultrafiltration membrane as well as preparation method and application thereof

The PEI@HPAN/COF nanofiber ultrafiltration membrane was prepared through needle-free electrospinning technology and carboxylation modification, which solved the problem of insufficient adsorption performance of the ultrafiltration membrane on heavy metal ions, achieved deep removal and selective adsorption of heavy metal ions, and improved the stability and anti-pollution performance of the membrane.

CN120268228APending Publication Date: 2025-07-08ANHUI XINHAI GAODAO NEW MATERIAL CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510530649.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

The existing ultrafiltration membranes have poor adsorption performance on heavy metal ions, making it difficult to achieve deep removal, and traditional nanofiber membranes have shortcomings in stability and selective adsorption.

Method used

The PEI@HPAN/COF nanofiber ultrafiltration membrane was prepared by needle-free electrospinning technology. By introducing COF materials on the surface of the fiber membrane and carboxylation modification, combining PEI with amide reaction with amino groups, a porous structure and rich functional groups were formed, and the adsorption ability to heavy metal ions was enhanced.

Benefits of technology

It significantly improves the adsorption performance and removal effect of heavy metal ions, especially the excellent removal ability for low-concentration heavy metal ions, realizes deep purification, and expands the application potential of membranes in the field of environmental purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120268228A_ABST
    Figure CN120268228A_ABST
Patent Text Reader

Abstract

The invention discloses a PEI-coated HPAN / COF nanofiber ultrafiltration membrane and a preparation method and application thereof, and belongs to the technical field of ultrafiltration membranes, the preparation method comprises the following steps: preparing a spinning solution from polyacrylonitrile, N, N-dimethylformamide and 1, 4-phenylenediamine; the preparation method comprises the following steps: carrying out needle-free electrostatic spinning, dipping an obtained fiber membrane in an absolute ethyl alcohol solution of trialdehyde phloroglucinol, taking out and cleaning, then completely dipping in an alkaline solution, taking out and washing, drying to obtain an HPAN / COF nanofiber membrane, dipping the HPAN / COF nanofiber membrane in a PE I solution for treatment, taking out, washing and drying to obtain a PE I-coated HPAN / COF nanofiber ultrafiltration membrane, and carrying out electrostatic spinning on the membrane to obtain the HPAN / COF nanofiber ultrafiltration membrane. Functional groups of the ultrafiltration membrane are combined with heavy metal ions through chemical modes such as chelation and electrostatic interaction, various heavy metals can be accurately removed, and the problem that a traditional ultrafiltration membrane is insufficient in heavy metal ion removal depth and breadth is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ultrafiltration membranes, and particularly relates to a PEI@HPAN / COF nanofiber ultrafiltration membrane and its preparation method and application. Background Art

[0002] With the rapid development of modern industry, the problem of water pollution has become increasingly severe and has become a global environmental challenge. Industrial production processes such as mining, metallurgy, electroplating, chemical engineering, electronics and other industries will produce a large amount of wastewater containing heavy metal ions. These heavy metal ions include lead (Pb), mercury (Hg), cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), etc. They have the characteristics of high toxicity, non-biodegradability and easy enrichment in organisms. Once heavy metal ions enter the water environment, they will cause serious damage to the aquatic ecosystem. They will affect the growth, metabolism and reproduction of microorganisms in water and disrupt the balance of the aquatic food chain. For example, high concentrations of mercury ions will inhibit the photosynthesis of aquatic plants, resulting in a decrease in the primary productivity of water bodies; while cadmium ions may interfere with the reproductive system of fish, reduce the reproductive ability of fish, and even lead to a sharp decline in the population of some fish species. For humans, long-term drinking or contact with water containing heavy metal ions will cause a series of serious health problems. Lead poisoning can damage the nervous system, blood system and kidneys, especially having an irreversible impact on the intellectual development and physical growth of children; mercury poisoning will damage the central nervous system, kidneys and immune system, causing serious diseases such as Minamata disease; cadmium poisoning mainly affects the kidneys and bones, resulting in osteoporosis, renal failure and other diseases. In addition, heavy metal ions may also accumulate in the human body through the transmission of the food chain, further increasing the health risks. Therefore, effectively removing heavy metal ions from wastewater is of extremely important significance for ensuring ecological environment safety and human health.

[0003] At present, the methods for treating heavy metal ions in wastewater mainly include chemical precipitation, ion exchange, adsorption, membrane separation, etc. Chemical precipitation is to add chemical agents to the wastewater to form insoluble precipitates of heavy metal ions for removal. However, this method has some drawbacks. For example, the use of precipitants may cause secondary pollution, and the removal effect for low-concentration heavy metal ions is not ideal, making it difficult to meet the increasingly strict environmental protection discharge standards. Ion exchange uses ion exchange resins to exchange with heavy metal ions in the wastewater to achieve the removal purpose. However, the regeneration process of ion exchange resins is relatively complex and costly. Moreover, when treating high-concentration heavy metal wastewater, the resins are prone to saturation and failure, requiring frequent replacement, which increases the treatment cost and operation difficulty. Adsorption is to use adsorbents to adsorb heavy metal ions to purify the wastewater. Common adsorbents include activated carbon, zeolite, biological adsorbents, etc. Although adsorption has the advantages of simple operation and relatively low cost, the adsorption capacity of adsorbents is limited, the adsorption selectivity is poor, and the regeneration and recycling after adsorption are difficult, which is prone to cause waste of adsorbents and secondary pollution. Membrane separation, as a new wastewater treatment technology, includes ultrafiltration, microfiltration, nanofiltration, and reverse osmosis, etc. Ultrafiltration membranes are usually used to remove macromolecular organic matter and colloidal particles in wastewater, but the removal effect for heavy metal ions is limited. It mainly relies on the sieving effect of the membrane, and the rejection rate of ions is relatively low. Traditional ultrafiltration membranes have limited surface functional groups and weak interaction with heavy metal ions, making it difficult to achieve deep removal of heavy metal ions.

[0004] Electrospinning technology, as an effective method for preparing nanofiber materials, has received extensive attention in recent years. This technology uses a high-voltage electrostatic field to make polymer solutions or melts overcome surface tension to form jets, and the jets are stretched, refined, and finally solidified to form nanofibers under the action of the electric field force. Electrospinning technology has the advantages of simple process, strong operability, and the ability to prepare nanofibers with a high specific surface area, small diameter, and porous structure. The prepared nanofiber membranes have shown great application potential in the fields of filtration, separation, biomedicine, sensors, etc. In the field of wastewater treatment, nanofiber membranes are expected to overcome some limitations of traditional membrane materials due to their unique structure and properties. For example, the high specific surface area of nanofiber membranes can provide more adsorption sites, which is beneficial to improving the removal efficiency of pollutants; their porous structure can reduce the mass transfer resistance of the membrane and increase the filtration flux. However, single-component nanofiber membranes still need to be further improved in some properties, such as the selective adsorption ability for specific pollutants, the stability and anti-fouling performance of the membrane, etc. Summary of the Invention

[0005] The purpose of the present invention is to provide a PEI@HPAN / COF nanofiber ultrafiltration membrane, its preparation method and application, to solve the problem of poor adsorption performance of heavy metal ions by ultrafiltration membranes in the prior art.

[0006] The object of the present invention can be achieved by the following technical solutions:

[0007] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, comprising the following steps:

[0008] S1. Add polyacrylonitrile to N,N-dimethylformamide, stir until completely dissolved, add 1,4-phenylenediamine, and stir evenly to obtain a spinning solution;

[0009] S2. Perform needleless electrospinning on the spinning solution to obtain a PAN / COF nanofiber membrane;

[0010] S3. Immerse the PAN / COF nanofiber membrane in an absolute ethanol solution of phloroglucinol trialdehyde for 30 - 60 min, then take it out and wash it with deionized water to obtain a PAN / COF composite fiber membrane;

[0011] S4. Completely immerse the PAN / COF composite fiber membrane in an alkaline solution, then take it out and wash it with deionized water until the washing liquid is neutral, and dry it to obtain an HPAN / COF nanofiber membrane;

[0012] S5. Dissolve polyethyleneimine in deionized water to obtain a PEI solution, soak the HPAN / COF nanofiber membrane in the PEI solution for treatment, take it out, wash it with deionized water, and dry it to obtain a PEI@HPAN / COF nanofiber ultrafiltration membrane.

[0013] The present invention first accurately prepares a spinning solution, uses a needleless electrospinning device to prepare a PAN / COF nanofiber membrane, then immerses it in an absolute ethanol solution of phloroglucinol trialdehyde to introduce a COF material into the fiber membrane. The COF material is a class of ordered porous organic materials with a high porosity, good chemical selectivity, and excellent structural stability. Then, the obtained membrane material is placed in an alkaline solution to convert the cyano group into a carboxyl group to complete the carboxylation modification. After that, a PEI solution is prepared, and PEI is fixed on the modified membrane through an amide reaction between the amino group and the carboxyl group to obtain a PEI@HPAN / COF nanofiber ultrafiltration membrane.

[0014] Further, in S1, the dosage ratio of polyacrylonitrile (PAN), N,N-dimethylformamide, and 1,4-phenylenediamine is 11 g: 89 g: 1 - 4 mmol.

[0015] Further, the specific operation steps of the needleless electrospinning in S2 are as follows:

[0016] The prepared spinning solution was transferred to the solution tank of the needle-free electrospinning equipment, the dehumidifier and exhaust fan were turned on, and the process parameters of the needle-free electrospinning equipment were set, the high-voltage electrostatic field strength was set to 30-50kV, the electrode spiral rotation speed was 10-20r / min, the receiving distance was 20-50cm, the spinning time was 60min, and the ambient temperature and humidity were set. After turning on the equipment, under the action of the high-voltage electrostatic field, the polymer solution formed a jet at the tip of the needle-free electrode. Due to the traction of the electric field force, the jet was continuously stretched and refined, and deposited on the receiving device to form a PAN / COF nanofiber membrane.

[0017] Furthermore, during the needle-free electrospinning process, the temperature is maintained at 20° C.-30° C., and the relative humidity is controlled at 30%-60%.

[0018] Furthermore, the mass ratio of trialdehyde phloroglucinol to anhydrous ethanol in S3 is 1:10.

[0019] Furthermore, the immersion process temperature in S4 is controlled to be 45-75°C and the time is 30-60 minutes.

[0020] Furthermore, the alkaline solution in S4 is a sodium hydroxide solution with a concentration of 0.5-1 mol / L.

[0021] Furthermore, the drying temperature in S4 is 40°C.

[0022] Furthermore, the immersion treatment temperature in S5 is 60° C., and the immersion treatment time is 12-24 hours.

[0023] Furthermore, the concentration of the PEI solution in S5 is 0.5-1.5 g / L.

[0024] A PEI@HPAN / COF nanofiber ultrafiltration membrane is prepared by the above preparation method.

[0025] Application of a PEI@HPAN / COF nanofiber ultrafiltration membrane in wastewater containing heavy metal ions.

[0026] Beneficial effects of the present invention:

[0027] 1. The present invention adopts needle-free electrospinning technology, which has a larger spinning area and no needle clogging problem compared to the traditional needle-based technology. It can form multiple spinning jets at the same time, greatly improving the production efficiency of PAN / COF nanofiber membranes, reducing production costs, making large-scale production more economical, and providing a new and efficient technical path for the industrialized large-scale manufacturing of nanofiber membranes, which is significantly advanced in the field of membrane preparation technology.

[0028] 2. The present invention uses polyacrylonitrile and 1,4-diphenylamine as raw materials to prepare a spinning solution, and then places the obtained membrane material in an absolute ethanol solution of phloroglucinol trialdehyde to introduce a COF material on the surface of the membrane material, preparing a PAN / COF composite fiber membrane with a hierarchical porous structure to solve the problem of insufficient adsorption performance of the PAN fiber membrane, and by regulating the loading amount of COF, exploring the optimal ratio, and obtaining an ultrafiltration membrane with better performance.

[0029] 3. The present invention modifies the cyano group to a carboxyl group in an alkaline solution for the PAN / COF composite fiber membrane. The reaction process is effectively regulated at a specific temperature during the modification process, and a large number of carboxyl functional groups are successfully introduced. Carboxylation not only improves the hydrophilicity of the membrane and reduces the risk of membrane fouling during wastewater treatment, but also provides abundant active sites for subsequent functional modification, enhancing the interaction basis between the membrane and metal ions, and expanding the application potential of the membrane in the field of environmental purification.

[0030] 4. The present invention firmly binds PEI to the surface of the HPAN / COF nanofiber membrane by means of the amide reaction between amino and carboxyl groups. The PEI@HPAN / COF structure constructed by this chemical bonding realizes the organic integration of the high specific surface area of the nanofiber membrane and the strong chelating performance of PEI. The two work synergistically to significantly enhance the adsorption and removal ability of heavy metal ions while ensuring the integrity of the membrane structure, creating an innovative mode for the functional optimization and expansion of composite ultrafiltration membranes.

[0031] 5. The ultrafiltration membrane of the present invention deeply purifies heavy metal ions by using abundant functional groups, which is different from traditional ultrafiltration membranes that rely only on physical sieving. The functional groups combine with heavy metal ions through chemical methods such as chelation and electrostatic interaction. This principle of deep purification endows the membrane with excellent removal effects on low-concentration heavy metal ions, can accurately remove various heavy metals, effectively solves the problems of insufficient depth and breadth of heavy metal ion removal by traditional ultrafiltration membranes, and provides innovative technical support for the deep treatment of wastewater. Description of the Drawings

[0032] The present invention will be further described below with reference to the drawings.

[0033] Figure 1 It is the SEM image of the PAN / COF nanofiber membrane in Example 1 of the present invention;

[0034] Figure 2 It is the SEM image of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained from Example 1 to Example 4 of the present invention;

[0035] Figure 3 It is the test result chart of the adsorption amount of chromium ions by the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained from Example 1 to Example 4 of the present invention;

[0036] Figure 4 It is the test result diagram of the adsorption capacity of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained in Example 5 - Example 10 of the present invention for chromium ions;

[0037] Figure 5 It is the test result diagram of the adsorption capacity of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained in Example 9 of the present invention for chromium ions, copper ions and ferric ions;

[0038] Figure 6 It is the test result diagram of the adsorption capacity of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained in Example 9 and Comparative Example 1 - Comparative Example 3 of the present invention for chromium ions. Specific Embodiments

[0039] In order to make the technical problems to be solved, technical solutions and beneficial effects of this application clearer, the following further details this application in combination with examples. It should be understood that the specific examples described here are only used to explain this application and are not used to limit this application.

[0040] In this application, "at least one" means one or more, and "a plurality" means two or more. "At least one (item)" or similar expressions thereof refer to any combination of these items, including any combination of single item (item) or multiple items (items). For example, "at least one (item) of a, b, or c", or, "at least one (item) of a, b, and c" can both represent: a, b, c, a~b (i.e., a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple respectively.

[0041] The terms used in the examples of this application are only for the purpose of describing specific implementation regulations and are not intended to limit this application. The singular forms "a", "the" and "this" used in the examples of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0042] It should be understood that in various examples of this application, the magnitude of the serial numbers of each process does not mean the sequence of execution. Some or all steps can be executed in parallel or sequentially. The execution sequence of each process should be determined by its function and internal logic and should not constitute any limitation to the implementation process of the examples of this application.

[0043] In the description of the embodiments of the present application, the weights of the relevant components mentioned not only can refer to the specific contents of each component, but also can represent the proportional relationship of the weights between each component. Therefore, as long as the contents of the relevant components in the description of the embodiments of the present application are enlarged or reduced in proportion, they are within the scope disclosed in the description of the embodiments of the present application. Specifically, the mass described in the description of the embodiments of the present application can be mass units well-known in the chemical industry such as μg, mg, g, kg, etc.

[0044] Unless otherwise defined, all the technical terms used hereinafter have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention.

[0045] Unless otherwise specifically stated, all kinds of raw materials, reagents, instruments, equipment, etc. used in the present application can be obtained through market purchase or can be prepared by existing methods.

[0046] Since the existing ultrafiltration membranes have poor adsorption performance for heavy metal ions, to solve the above problems to a certain extent, the first aspect of the embodiments of the present application provides a preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, including the following steps:

[0047] S1. Add polyacrylonitrile into N,N-dimethylformamide, stir until completely dissolved, add 1,4-phenylenediamine, and stir evenly to obtain a spinning solution;

[0048] S2. Perform needleless electrospinning on the spinning solution to obtain a PAN / COF nanofiber membrane;

[0049] S3. Immerse the PAN / COF nanofiber membrane in an absolute ethanol solution of phloroglucinol trialdehyde for 30 - 60 min, then take it out and wash it with deionized water to obtain a PAN / COF composite fiber membrane;

[0050] S4. Completely immerse the PAN / COF composite fiber membrane in an alkaline solution, then take it out and wash it with deionized water until the washing liquid is neutral, and dry it to obtain an HPAN / COF nanofiber membrane;

[0051] S5. Dissolve polyethyleneimine in deionized water to obtain a PEI solution, soak the HPAN / COF nanofiber membrane in the PEI solution for treatment, take it out, wash it with deionized water, and dry it to obtain a PEI@HPAN / COF nanofiber ultrafiltration membrane.

[0052] This application provides a needleless electrospun PEI@HPAN / COF nanofiber ultrafiltration membrane for deeply removing heavy metal ions from wastewater. First, a precursor is obtained by blending a COF-binding monomer with PAN, and then, in combination with the in-situ growth method, a porous COF material is grown on the fiber surface to prepare a PAN / COF composite fiber membrane with a hierarchical porous structure. To address the insufficient adsorption performance of the PAN fiber membrane, the optimal ratio is explored by regulating the COF loading. Subsequently, it is placed in an alkaline solution to convert the cyano group into a carboxyl group to complete the carboxylation modification. Then, a PEI solution is prepared, and PEI is fixed on the modified membrane through the amide reaction between the amino group and the carboxyl group.

[0053] Further, in S1, the dosage ratio of polyacrylonitrile (PAN), N,N-dimethylformamide, and 1,4-phenylenediamine is 11 g: 89 g: 1-4 mmol.

[0054] Further, the specific operating steps of the needleless electrospinning in S2 are as follows:

[0055] Transfer the prepared spinning solution to the solution tank of the needleless electrospinning equipment, turn on the dehumidifier and the exhaust fan, and set the process parameters of the needleless electrospinning equipment. The high-voltage electrostatic field strength is set to 30-50 kV, the electrode spiral rotation speed is 10-20 r / min, the receiving distance is 20-50 cm, the spinning time is 60 min, and conditions such as the environmental temperature and humidity are set. After starting the equipment, under the action of the high-voltage electrostatic field, the polymer solution forms a jet at the tip of the needleless electrode. Due to the traction of the electric field force, the jet is continuously stretched and refined, and a PAN / COF nanofiber membrane is deposited on the receiving device.

[0056] Further, during the needleless electrospinning process, the temperature is maintained at 20°C - 30°C, and the relative humidity is controlled at 30% - 60%.

[0057] Further, in S3, the mass ratio of phloroglucinol trialdehyde and absolute ethanol is 1:10.

[0058] Further, in S4, the temperature during the immersion process is controlled at 45-75°C, and the time is 30-60 min.

[0059] Further, in S4, the alkaline solution is a sodium hydroxide solution with a concentration of 0.5-1 mol / L.

[0060] Further, in S4, the drying temperature is 40°C.

[0061] Further, in S5, the immersion treatment temperature is 60°C, and the immersion treatment time is 12-24 h.

[0062] Further, in S5, the concentration of the PEI solution is 0.5-1.5 g / L.

[0063] In some embodiments, the concentration of the PEI solution in S4 is 0.5 g / L, 1 g / L, 1.5 g / L and other typical but non-limiting concentrations or the range between any two concentrations. Within this range, the HPAN / COF nanofiber membrane has better binding with polyethyleneimine, which is beneficial to obtaining an ultrafiltration membrane with better adsorption performance. If the concentration of the PEI solution is too low, fewer amino groups are introduced on the HPAN / COF nanofiber membrane, resulting in poor binding performance with heavy metal ions. If the concentration of the PEI solution is too high, first, there are limited adsorption sites on the HPAN / COF nanofiber membrane and it is impossible to bind with too much polyethyleneimine, leading to waste of reagents. Second, the introduction of too much polyethyleneimine consumes a large amount of carboxyl groups, resulting in a significant decrease in the carboxyl content on the surface of the ultrafiltration membrane. It is difficult to improve the adsorption performance of the ultrafiltration membrane through the interaction between carboxyl groups and metal ions, which will also lead to poor adsorption performance of the ultrafiltration membrane for metal ions.

[0064] The second aspect of the embodiments of the present application provides a PEI@HPAN / COF nanofiber ultrafiltration membrane prepared by the above preparation method.

[0065] The third aspect of the embodiments of the present application provides an application of the PEI@HPAN / COF nanofiber ultrafiltration membrane in wastewater containing heavy metal ions.

[0066] The following specific embodiments and comparative examples are used to illustrate the technical solutions of the present application. In the embodiments and comparative examples, the molecular weight of polyethyleneimine is 10,000, and the M W of polyacrylonitrile is 150,000.

[0067] Example 1

[0068] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane includes the following steps:

[0069] S1. Add polyacrylonitrile to N,N-dimethylformamide and stir until the polymer is completely dissolved to obtain a solution with a mass fraction of 11%. Subsequently, add 3 mmol of 1,4-phenylenediamine and stir evenly to obtain a spinning solution.

[0070] S2. Transfer the spinning solution to the solution tank of a needleless electrospinning device, turn on the dehumidifier and exhaust fan, and set the process parameters of the needleless electrospinning device to perform needleless electrospinning to obtain a PAN / COF nanofiber membrane.

[0071] The high-voltage electrostatic field strength is set to 30 kV, the electrode spiral rotation speed is 10 r / min, the receiving distance is 20 cm, the spinning time is 60 min, the temperature is maintained at 20 °C, and the relative humidity is controlled at 30%.

[0072] The obtained PAN / COF nanofiber membrane was observed by scanning electron microscopy, and the results are as Figure 1 shown, Figure 1 clearly presenting the fine structure of the fibers. Figure 1 The surface of the fibers in Figure 1 is smooth, the diameter distribution is uniform, and there are no obvious adhesions or defects, indicating that the needleless spinning technology effectively avoids the problem of droplet residue easily generated by traditional needle spinning by optimizing parameters such as voltage, liquid supply speed, and receiving distance, and achieves high consistency in large-scale production;

[0073] S3. After immersing the PAN / COF nanofiber membrane in an absolute ethanol solution of phloroglucinol trialdehyde for 30 min, the mass ratio of phloroglucinol trialdehyde to absolute ethanol is 1:10. It is taken out and washed with deionized water to obtain a PAN / COF composite fiber membrane;

[0074] S4. The PAN / COF composite fiber membrane is completely immersed in a sodium hydroxide solution with a concentration of 0.5 mol / L and treated at 60 °C for 60 min. Then it is taken out and washed with deionized water until the washing liquid is neutral, and dried to a constant weight at 40 °C to obtain an HPAN / COF nanofiber membrane;

[0075] S5. Polyethyleneimine is dissolved in deionized water to obtain a PEI solution with a concentration of 0.5 g / L. The HPAN / COF nanofiber membrane is immersed in the PEI solution and treated at 60 °C for 12 h. Then it is taken out, washed with deionized water, and dried to a constant weight at 40 °C to obtain a PEI@HPAN / COF nanofiber ultrafiltration membrane.

[0076] Example 2

[0077] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the difference is only that the addition amount of 1,4-phenylenediamine in Example 1 is adjusted from "3 mmol" to "1 mmol".

[0078] Example 3

[0079] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the difference is only that the addition amount of 1,4-phenylenediamine in Example 1 is adjusted from "3 mmol" to "2 mmol".

[0080] Example 4

[0081] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the difference is only that the addition amount of 1,4-phenylenediamine in Example 1 is adjusted from "3 mmol" to "4 mmol".

[0082] The obtained PEI@HPAN / COF nanofiber ultrafiltration membranes from Example 1 to Example 4 were observed using a scanning electron microscope, and the results are as follows. Figure 2 As shown in Figure 2 , a and a' represent Example 2, b and b' represent Example 3, c and c' represent Example 1, and d and d' represent Example 4. Figure 2 It clearly presents the uniform distribution and surface morphology of the fibers. From Figure 2 , it can be significantly observed that when the doping amount of 1,4-phenylenediamine (Pa) is 1 - 3 mmol, the amount of in-situ grown COF on the fibers gradually increases. When the doping amount is 3 mmol, the amount of COF is the largest. However, when the doping amount is 4 mmol, the amount of in-situ grown COF on the fibers does not increase but decreases. It may be that the excessive doping amount of Pa causes Pa in the fibers to dissolve in ethanol before growing into COF and then reacts with Tp to form COF, but not on the fibers. The small amount of COF on the fibers is caused by the attachment of COF in the solution.

[0083] Example 5

[0084] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the only difference is that in this example, during needleless electrospinning, the high-voltage electrostatic field intensity is set to 35 kV, the electrode spiral rotation speed is 15 r / min, the receiving distance is 30 cm, and the spinning time is 60 min.

[0085] Example 6

[0086] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the only difference is that in this example, during needleless electrospinning, the high-voltage electrostatic field intensity is set to 40 kV, the electrode spiral rotation speed is 15 r / min, the receiving distance is 40 cm, and the spinning time is 60 min.

[0087] Example 7

[0088] A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, compared with Example 1, the only difference is that in this example, during needleless electrospinning, the high-voltage electrostatic field intensity is set to 45 kV, the electrode spiral rotation speed is 20 r / min, the receiving distance is 45 cm, and the spinning time is 60 min.

[0089] Example 8

[0090] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 1, the only difference is that when there is no needle electrospinning in this example, the high-voltage electrostatic field intensity is set to 50 kV, the electrode spiral rotation speed is 15 r / min, the receiving distance is 15 cm, and the electrospinning time is 60 min.

[0091] Example 9

[0092] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 1, the only difference is that the concentration of the PEI solution in S5 of Example 1 is adjusted from "0.5 g / L" to "1.0 g / L".

[0093] Example 10

[0094] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 1, the only difference is that the concentration of the PEI solution in S5 of Example 1 is adjusted from "0.5 g / L" to "1.5 g / L".

[0095] Comparative Example 1

[0096] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 9, the only difference is that the addition amount of 1,4-phenylenediamine in Example 9 is adjusted from "3 mmol" to "0 mmol".

[0097] Comparative Example 2

[0098] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 9, the only difference is that the concentration of the PEI solution in S5 of Example 9 is adjusted from "0.5 g / L" to "0.3 g / L".

[0099] Comparative Example 3

[0100] A preparation method of PEI@HPAN / COF nanofiber ultrafiltration membrane. Compared with Example 9, the only difference is that the concentration of the PEI solution in S5 of Example 9 is adjusted from "1.5 g / L" to "2.0 g / L".

[0101] Explore the effect of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained from Implementation Cases 1 - 4 on the static adsorption of heavy metal ion solutions. During the adsorption experiment, 20 mg of the PEI@HPAN / COF nanofiber ultrafiltration membrane was added to 20 mL of a heavy metal ion solution with a concentration of 200 mg / L. The heavy metal ion was hexavalent chromium. The pH was controlled at 2, and the solution was oscillated at 120 rpm for 6 hours at a constant temperature (303K). Inductively coupled plasma mass spectrometry (ICP) was used to detect the residual concentration of the heavy metal ion solution after equilibrium adsorption, and the removal efficiency of the solution for the heavy metal ion solution was investigated. Calculate the adsorption capacity Qe (mg / g):

[0102] where Q e is the adsorption capacity (mg / g) of the adsorption equilibrium fiber ultrafiltration membrane; C0 and C e are the initial and post-adsorption equilibrium Cr(VI) concentrations (mg / L), V is the volume (L) of the Cr(VI) solution used, and m is the mass (g) of the fiber membrane used.

[0103] The test results are as Figure 3 shown. It can be seen from Figure 3 that the adsorption performance of the PEI@HPAN / COF nanofiber ultrafiltration membranes obtained from Implementation Cases 2, 3, and 4 for chromium ions is similar, and all are lower than that of Implementation Case 1. The reason is that the COF growth state of the ultrafiltration membrane in Implementation Case 1 is the best, while the COF growth of other PAN / COF nanofiber ultrafiltration membranes is incomplete or exfoliated, which is consistent with Figure 2 the SEM images of different PAN / COF composite fiber membranes.

[0104] According to the above method, explore the effect of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained from Implementation Cases 5 - 10 on the static adsorption of chromium ion solutions. The test results are as Figure 4 shown. It can be seen from Figure 4 that there are significant differences in the adsorption capacities under different preparation conditions. Implementation Cases 5 - 10 correspond to different electrospinning process parameters and PEI solution concentrations, and these factors have an important impact on the adsorption performance.

[0105] First of all, the change of electrospinning process parameters significantly affects the structure and performance of the nanofiber membrane. For example, the increase in the high-voltage electrostatic field strength (from 30 kV to 50 kV) and the adjustment of the receiving distance (from 20 cm to 45 cm) may lead to changes in the fiber diameter and membrane porosity, thereby affecting the adsorption capacity. A higher electrostatic field strength and an appropriate receiving distance contribute to the formation of a more uniform nanofiber structure, increasing the adsorption surface area and adsorption efficiency.

[0106] Secondly, the change in the concentration of the PEI solution also has a significant impact on the adsorption capacity. From Example 1, Example 9, and Example 10, the PEI concentration increases from 0.5 g / L to 1.5 g / L. As the PEI concentration increases, the number of amino functional groups on the surface of the nanofiber membrane increases, which enhances the chemical adsorption ability of the membrane for heavy metal ions.

[0107] In addition, taking Example 9 as a test case, the adsorption capacity of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained in Example 9 for divalent copper (Cu 2+ ) and trivalent iron (Fe 3+ ) was tested. The testing process referred to the chromium ion adsorption capacity Qe, with the difference being the heavy metal ions. The test results are as Figure 5 shown. As can be seen from Figure 5 , the adsorption capacity of the PEI@HPAN / COF nanofiber ultrafiltration membrane for hexavalent chromium (Cr(VI)), divalent copper (Cu 2+ ) and trivalent iron (Fe 3+ ) shows significant differences, which is closely related to its adsorption mechanism. The following is a specific analysis of the adsorption mechanism:

[0108] ① Adsorption mechanism of hexavalent chromium (Cr(VI))

[0109] Electrostatic adsorption and chemical reduction: Under acidic conditions (pH = 2), hexavalent chromium mainly exists in the form of anions (such as Cr2O7 2- or HCrO4 - ). The protonated amino group (-NH3 + ) in the PEI molecule adsorbs with the Cr(VI) anion through electrostatic interaction; the amino and imino functional groups of COF are highly protonated under strong acidic conditions, with a large amount of positive charge on the surface, and Cr(VI) exists as HCrO4 with a high charge density in a strong acid environment - , resulting in strong electrostatic attraction and adsorption; in addition, the amino group of PEI may reduce part of the Cr(VI) to Cr(Ⅲ), further enhancing the adsorption effect.

[0110] Function of functional groups: The carboxyl group (-COOH) and amino group (-NH2) on the surface of the PEI@HPAN / COF membrane provide abundant adsorption sites, forming stable chemical bonds with Cr(VI), thereby increasing the adsorption capacity.

[0111] ② Adsorption mechanism of divalent copper (Cu 2+ )

[0112] Coordination effect: Cu 2+is a typical transition metal ion with empty d orbitals, which can coordinate with the amino groups (-NH2) in the PEI molecule and the carboxyl groups (-COOH) on the membrane surface to form stable complexes.

[0113] Electrostatic adsorption: Under acidic conditions, after the amino groups of PEI are protonated (-NH3 + ), the electrostatic repulsion between them and the positively charged Cu 2+ is weak, but the coordination effect dominates, so the adsorption capacity is high.

[0114] ③ Adsorption mechanism of ferric ion (Fe 3+ )

[0115] Coordination and electrostatic adsorption: Fe 3+ has a high charge density and empty d orbitals, which can strongly coordinate with the amino groups of PEI and the carboxyl groups on the membrane surface. At the same time, the electrostatic adsorption between Fe 3+ and the protonated amino groups also plays a certain role.

[0116] Hydrolysis: Under acidic conditions, Fe 3+ may be partially hydrolyzed to form Fe(OH) 2+ or Fe(OH) 2+ , and these hydrolysis products adsorb with the functional groups on the membrane surface, further increasing the adsorption capacity.

[0117] ④ Reasons for the difference in adsorption capacity

[0118] Ion characteristics: Cr(VI) exists in the form of anions and has a strong electrostatic interaction with protonated amino groups, with the highest adsorption capacity; Cu 2+ and Fe 3+ are adsorbed through coordination, but Fe 3+ has a higher charge density and stronger coordination ability, so the adsorption capacity is higher than that of Cu 2+ .

[0119] Functional group density: The carboxyl and amino group densities on the surface of the PEI@HPAN / COF membrane are relatively high, providing sufficient adsorption sites for different heavy metal ions, but the adsorption mechanisms and affinities of different ions lead to differences in adsorption capacity.

[0120] ⑤ Performance advantages of the membrane

[0121] Multifunctional adsorption: The PEI@HPAN / COF membrane can efficiently remove various heavy metal ions through multiple mechanisms such as electrostatic adsorption, coordination, and chemical reduction.

[0122] In summary, Figure 5The adsorption capacity of hexavalent chromium is the highest, mainly attributed to electrostatic adsorption and chemical reduction; the adsorption capacities of divalent copper and trivalent iron are the second, mainly relying on coordination. The PEI@HPAN / COF membrane realizes the deep removal of heavy metal ions in wastewater through rich functional groups and multiple adsorption mechanisms, and has broad application prospects.

[0123] The influence of the PEI@HPAN / COF nanofiber ultrafiltration membrane obtained by exploring Example 9 and Comparative Examples 1-3 according to the above method on the static adsorption of chromium ion solution was investigated, and the test results are as Figure 6 shown. It can be seen from the Figure 6 test results in that the absence of 1,4-phenylenediamine in the spinning solution leads to the inability to form COF on the final ultrafiltration membrane, seriously affecting the adsorption effect. Too low or too high PEI concentration will seriously affect the adsorption performance of the ultrafiltration membrane.

[0124] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article or device.

[0125] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane, characterized in that, It includes the following steps: S1. Add polyacrylonitrile into N,N-dimethylformamide, stir until completely dissolved, add 1,4-phenylenediamine, and stir evenly to obtain a spinning solution; S2. Perform needleless electrospinning on the spinning solution to obtain a PAN / COF nanofiber membrane; S3. Immerse the PAN / COF nanofiber membrane in an absolute ethanol solution of phloroglucinol trialdehyde for 30 - 60 min, then take it out and wash it with deionized water to obtain a PAN / COF composite fiber membrane; S4. Completely immerse the PAN / COF composite fiber membrane in an alkaline solution, then take it out and wash it with deionized water until the washing liquid is neutral, and dry it to obtain an HPAN / COF nanofiber membrane; S5. Immerse the HPAN / COF nanofiber membrane in a PEI solution for treatment, take it out, wash it with deionized water, and dry it to obtain a PEI@HPAN / COF nanofiber ultrafiltration membrane.

2. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S1, the dosage ratio of polyacrylonitrile, N,N-dimethylformamide, and 1,4-phenylenediamine is 11 g : 89 g : 1 - 4 mmol.

3. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S2, the process parameters of needleless electrospinning are: the high-voltage electrostatic field strength is set at 30 - 50 kV, the electrode spiral rotation speed is 10 - 20 r / min, the receiving distance is 20 - 50 cm, and the spinning time is 60 min.

4. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S3, the mass ratio of phloroglucinol trialdehyde to absolute ethanol is 1 :

10.

5. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S4, the temperature during the immersion process is controlled at 45 - 75 °C, and the time is 30 - 60 min.

6. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S4, the alkaline solution is a sodium hydroxide solution with a concentration of 0.5 - 1 mol / L.

7. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that, In S5, the immersion treatment temperature is 60 °C, and the immersion treatment time is 12 - 24 h.

8. The preparation method of a PEI@HPAN / COF nanofiber ultrafiltration membrane according to claim 1, characterized in that In S5, the concentration of the PEI solution is 0.5 - 1.5 g / L.

9. A PEI@HPAN / COF nanofiber ultrafiltration membrane, characterized in that, Prepared by the preparation method according to any one of claims 1 - 8.

10. Application of a PEI@HPAN / COF nanofiber ultrafiltration membrane as described in claim 9 in wastewater containing heavy metal ions.

Citation Information

Cited By

  • UiO-66 grafted composite ultrafiltration membrane as well as preparation method and application thereof

    CN121060314A